Acylcarnitine esters profiling of serum and follicular fluid in patients undergoing in vitro fertilization - Várnagy, Ákos (BioMed Central, 2013)
BACKGROUND: L-carnitine-mediated beta-oxidation of fatty acids has a well established role in energy supply of oocytes and embryos. Disturbed carnitine metabolism may impair the reproductive potential in IVF and can serve as a biomarker of pregnancy outcome. METHODS: Our study was performed between March 24, 2011 and May 9, 2011. We performed 44 unselected IVF cycles, (aged 23–40 years (mean: 32.3+/−5.1 years) and had BMI of 17.3-34.7 (mean: 23.80+/−4.9). Samples were also obtained from 18 healthy women of similar age admitted for minor elective surgery to serve as control for plasma carnitine profile. Serum and follicular fluid (FF) free carnitine (FC) and 20 major acylcarnitines (ACs) were measured by ESI/MS/MS method. RESULTS: Serum FC and AC levels in IVF patients were comparable to those in healthy control women. In FF FC and short-chain AC concentrations were similar to those in maternal serum, however, the levels of medium-chain, and long-chain AC esters were markedly reduced (p<0.05). The serum to FF ratio of individual carnitine compounds increased progressively with increasing carbon chain length of AC esters (p<0.05). There was a marked reduction in total carnitine, FC and AC levels of serum and FF in patients with oocyte number of >9 and/or with embryo number of >6 as compared to the respective values of <9 and/or <6 (p<0.05). CONCLUSIONS: In IVF patients with better reproductive potential the carnitine/AC pathway appears to be upregulated that may result in excess carintine consumption and relative depletion of carnitine pool. Consequently, IVF patients may benefit from carnitine supplementation.